Medicine residues in milk and the MilkSure initiative. (2nd January 2019) - Atkinson, Owen
Abstract : Dairy farmers and their veterinary surgeons are under some scrutiny currently regarding medicine stewardship on dairy farms. There are several streams of activity within the industry, mainly focused on reducing antibiotic resistance. Avoiding medicine residues in milk is a separate stream of activity, the main thrust of which is through the Dairy UK/BCVA MilkSure initiative. Residues and the tests used to detect them are far from straightforward and misunderstandings are not uncommon. This article gives context to the subject of milk residues and summarises the main points which are useful for practitioners to know.